CASE REPORT WAARDENBURG SYNDROME TYPE I WITH IRIS AND RETINAL COLOBOMA - Atina Yustisia Lestari; Reni Prastyani (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2020)
We present a rare case report, Waardenberg syndrome type I, and ocular abnormalities related to the disease. A Boy, 11 months, presented with blue and hole in inferior iris. Patien also controlled to pediatric and ENT departement according his global developmental delayed, and unresponsiveness to sound stimulus since birth. Patient presented with distophia cantrorum, bilateral iris coloboma, brilliant blue iris, and retinal coloboma. Others systemic condition were skin hypopigmentation, bilateral sensorineural hearing lost, and global developmental delay equal to 6 months old baby. According to manifestations, this supporting diagnosis for Waardenberg syndrome type I. The management consists in treating the symptoms accordingly. Careful follow up and work up is important to improve patient quality of life